Anionic states of resveratrol and its subunits - Miranda, Ely Giancoli Ferreira de (2021)
We report the first characterization of the anion states related to the dissociative processes in two compounds, Resveratrol (RV) and Resorcinol (RS), employing both scattering and bound states techniques. RV is a very challenging system for this kind of study in view of its size. Our results point out a valence bound state, three shape resonances and a mixed-character resonance. The zero-energy thresholds reported elsewhere and the presently calculated resonance spectrum are consistent with the mass spectroscopy data. In particular, with the production of H2 (reaction that could account for the antioxidant activity) at nearly zero energy which could proceed from a vibrational Feshbach resonances arising from a valence bound state. We also investigated the RS subunit of the RV, which could be a less computationally expensive prototype for the production of H2. We obtained two shape resonances and a mixed-character resonance. There is a correspondence between the anion states of RV and RS, and even between the thresholds, but the lack of anion bound states for the smaller molecules should suppress the H2-formation channel at 0 eV.